Role of architectural historical precedent in aesthetic design of contemporary architecture: Safavid architecture / Bahram Shahedi, Nila Keumala, Naziaty Mohd Yaacob - Shahedi, Bahram; Keumala, Nila; Mohd Yaacob, Naziaty (Faculty of Architecture, Planning & Surveying and UiTM Press, 2013)
This study essentially examined the architecture of historical precedent of Iranian architecture, and focused on Safavid Architecture from experts' perspective. The study is mainly qualitative in nature, and explained, why historical precedent is important and how it could be applicable to the formation of aesthetic design in contemporary architecture. We collected the data through semi-structured interview with experts, which were guided by the literature and theoretical foundation. The account of the interviews was recorded, transcribed and the content analyzed, examined and evaluated for evidence. Three themes emerged, including aesthetic design attributes, aesthetic design values and application of architectural precedent in the aesthetic design of contemporary architecture. We discussed the themes in the light of the research questions; following drew a conclusion, which recognized the most perceivable concepts as to be applicable in the design aesthetic of contemporary architecture. In addition, it has theorized that the reality and essence of a social phenomenon in the contemporary architecture is in the character of architectural precedent.